The Classification of Data: A Novel Artificial Neural Network (ANN) Approach through Exhaustive Validation and Weight Initialization - Tripathi, Kshitij; Vyas, Rajendra G; Gupta, Anil K (International Journal of Computer Sciences and Engineering, 2025)
The Artificial Neural Networks (ANNs) has proved their significance to perform well in the fields of data-mining and machine learning like classification, pattern recognition, forecasting and prediction to have a few of them. This paper explores a novel approach for classification of data on four benchmark datasets from the perspective of ANNs and its intricacies. The proposed approach is successful in overcoming the drawback of over-fitting of data exists in the classification domain. Further, the proposed methodology reflects very improved and consistent results in comparison to existing techniques available in the ANNs as well as non-ANN domain.